Electrical conductivity of LTA‐zeolite in the presence of poly(vinyl alcohol) and poly(vinyl pyrrolidone) polymers. Issue 11 (4th June 2013) - Salimian, Maryam; Okhay, Olena; Krishna, Rahul; Titus, Elby; Gracio, José; Guerra, Luís; Ventura, João; Freire, Cristina; Pereira, Clara; Babu, P. Ramesh; Khairnar, Rajendra S.
<x xml:space="preserve">Abstract</x> The electrical behavior of PVA/ Zeolite and PVP/ Zeolite composite thin films are studied. The results show that the conductivity properties are composition ratio‐dependent and also related to the type of polymers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>